2022
DOI: 10.3390/children9081193
|View full text |Cite
|
Sign up to set email alerts
|

Is the Leptin/Adiponectin Ratio a Better Diagnostic Biomarker for Insulin Resistance than Leptin or Adiponectin Alone in Adolescents?

Abstract: Background: Recently, the leptin/adiponectin (L/A) ratio has been suggested as a novel predictor of cardio-metabolic and other chronic diseases. Aim: To evaluate the ability of leptin (L), adiponectin (A), and the L/A ratio in identifying high risk of insulin resistance IR in adolescents, adjusted by cardiorespiratory fitness, adherence to the Mediterranean diet, and body fat percentage. Subjects and methods: This is a cross-sectional analysis with 529 adolescents aged 12–18 years-old. Blood samples were taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The association between LAR and insulin resistance was mainly driven by leptin over adiponectin in the present study, given that we found a weak association between plasma adiponectin and insulin resistance. In this context, increased leptin level, a common finding in obesity, is strongly associated with insulin resistance partially through increased adiposity, which suggests an overall decrease in sensitivity to leptin and insulin in obesity ( 38 ). Notably, the children in our study were prepubertal (Tanner 1) and had approximately 7 years of age (before the known rise in plasma insulin of adolescence), which may explain the nonsignificant results for the association between plasma adiponectin and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between LAR and insulin resistance was mainly driven by leptin over adiponectin in the present study, given that we found a weak association between plasma adiponectin and insulin resistance. In this context, increased leptin level, a common finding in obesity, is strongly associated with insulin resistance partially through increased adiposity, which suggests an overall decrease in sensitivity to leptin and insulin in obesity ( 38 ). Notably, the children in our study were prepubertal (Tanner 1) and had approximately 7 years of age (before the known rise in plasma insulin of adolescence), which may explain the nonsignificant results for the association between plasma adiponectin and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that, in adolescents, leptin and LAR are associated with high insulin resistance independent of potential confounders (age, sex, pubertal stage, adherence to the Mediterranean diet, cardiorespiratory fitness, and body fat percentage) ( 47 ). These results are consistent with those of the present study, where we found a high risk of insulin resistance associated with leptin and LAR.…”
Section: Discussionmentioning
confidence: 99%
“…These inflammatory cytokines induce insulin resistance by activating the suppressors of cytokine signaling proteins in insulin-target tissues ( 73 ). Both leptin and adiponectin are important in obesity through indirect regulation of food intake and body weight ( 74 ). In fact, leptin reduces body weight by decreasing food intake.…”
Section: Effect Of C Olitorius On the Body Weight ...mentioning
confidence: 99%
“…Thus, adipocytes are regarded as a significant source of chronic low-grade inflammation. Endothelial cells release excessive amounts of cell adhesion molecules (CAMs), such as vascular cell adhesion molecule-1 (VCAM-1), intercellular adhesion molecule-1 (ICAM-1), and E-selectin in response to subclinical inflammation, resulting in leukocyte mobilization and adherence to the endothelium [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous hormone-dependent cancers are associated with a lower adiponectin concentration, i.e., breast, endometrial, and prostate [ 22 , 23 , 24 ]. Thus, the leptin-to-adiponectin ratio (LAR) was established as a sensitive systemic inflammatory marker and predictor of cardiometabolic and neoplastic disease outcomes [ 7 ]. Since, Słomian et al observed that lower LAR was associated with a longer survival rate and better therapy response.…”
Section: Introductionmentioning
confidence: 99%